2016
DOI: 10.1590/s1679-45082016ao3708
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors with mammographic changes in women undergoing breast cancer screening

Abstract: Objective:To evaluate association of sociodemographic, anthropometric, and epidemiological factors with result of mammogram in women undergoing breast cancer screening.Methods:This is a cross-sectional study with data obtained through interviews, anthropometric measurements, and mammography of 600 women aged 40 to 69 years at the Preventive Medicine Department of Hospital de Câncer de Barretos, Brazil, in 2014. The results of these examinations in the BI-RADS categories 1 and 2 were grouped and classified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…It is particularly more useful than DM in locating small, non-palpable lesions in women with dense breast tissue. 31 In the Somolnsight study, it has also been shown to be a useful adjunctive modality in breast cancer screening by detecting more cancers in conjunction with mammography as opposed to mammography alone. 32 No studies show that BUs improve detection over MRIs.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly more useful than DM in locating small, non-palpable lesions in women with dense breast tissue. 31 In the Somolnsight study, it has also been shown to be a useful adjunctive modality in breast cancer screening by detecting more cancers in conjunction with mammography as opposed to mammography alone. 32 No studies show that BUs improve detection over MRIs.…”
Section: Resultsmentioning
confidence: 99%
“…Health promotion actions should be sought to improve the practice of healthy eating, not only for cancer patients, but in both groups. SANT'ANA et al, 2016;INCA, 2017b).…”
Section: Manfrin; Negri 2008mentioning
confidence: 99%
“…As anormalidades nos números de cromossomos podem ser correlacionadas ao aumento da idade materna, que é uma das causas de risco para tumores do SNC em crianças (GUERRA et al, 2008). Silva et al (2016) observaram que, entre a sua amostra de câncer do SNC (n= 119), 13 casos e 13 controles apresentaram anomalia congênita no nascimento.…”
Section: Fatores Maternos E Do Nascimentounclassified
“…Relacionado ao câncer de mama (CM) em mulheres, os exames mais eficientes para detecção da doença são: mamografia, ultrassonografia e ressonância magnética. Apesar da mamografia constatar lesões subclínicas (SANT'ANA et al, 2016).…”
Section: Introductionunclassified